Order and control in the environment: exploring the effects on undesired behaviour and the importance of locus of control - Jansen, Anja M. (Legal and criminological psychology, 2017)
Purpose. This study aimed at gaining more insight into the combined influence of environmental factors and personal vulnerability to environmental cues on cheating behaviour in a task-related indoor setting. We propose that a disorderly environment increases cheating as it implicitly signals that undesirable behaviours are common. Camera presence is expected to buffer these effects. We included locus of control (LOC) as a personality variable, as we expected individuals with an external LOC to be more susceptible by environmental cues. Methods. Seventy-six students participated in a 2 (orderly vs. disorderly environment) × 2 (camera vs. no camera present) experiment with cheating as the main dependent variable. We established the individual participant's LOC (Rotter, 1966, Psychol. Monogr., 80, 1) in a separate session. Results. Findings did indeed show that individuals with an external LOC cheated more in a disorderly rather than an orderly environment. We also found an interaction effect with LOC suggesting this effect was particularly present for participants having an external rather than internal LOC. Camera presence did not yield significant main or interaction effects. Conclusion. These findings confirm the importance of environmental design for behaviour regulation as well as the moderating influence of personality makeup.